Incidence of SARS-CoV-2 infection in health care workers from Northern Italy based on antibody status: immune protection from secondary infection- A retrospective observational case-controlled study. (August 2021) - Rovida, Francesca; Cassaniti, Irene; Percivalle, Elena; Sarasini, Antonella; Paolucci, Stefania; Klersy, Catherine; Cutti, Sara; Novelli, Viola; Marena, Carlo; Luzzaro, Francesco; De Vito, Giovanni; Schiavo, Roberta; et al.
Highlights: Immunity from natural SARS-CoV-2 infection is protective in healthcare workers Secondary infection is associated with low or absent serum neutralizing titer Anti-Spike IgG were not significantly lower in subjects with secondary infections Secondary infection is usually asymptomatic or mildly symptomatic Vaccination of SARS-CoV-2-seronegative subjects might be prioritized Abstract: Objective: The protection from SARS-CoV-2 infection induced by SARS-CoV-2 anti-S1 and anti-S2 IgG antibody positivity resulting from natural infection was evaluated. Methods: The frequency of SARS-CoV-2 infection (as determined by virus RNA detection) was evaluated in a group of 1, 460 seropositive and a control group of 8, 150 seronegative healthcare workers in three Centres of Northern Italy in the period June-November 2020. Neutralizing serum titers were analyzed in seropositive subjects with or without secondary SARS-CoV-2 infection. Results: During the 6-month survey, 1.78% seropositive subjects developed secondary SARS-CoV-2 infection while 6.63% seronegative controls developed primary infection (odds ratio: 0.26; 95% confidence interval: 0.17-0.38). Secondary infection was associated with low or absent serum neutralizing titer (p<0.01) and was mildly symptomatic in 45.8% cases vs 71.4% symptomatic primary infections (odds ratio: 0.34; 95% confidence interval: 0.16-0.78). Conclusions: Immunity from natural infection appears protective from secondary infection; therefore, vaccination of seronegative subjects might be prioritized.